Qualidade fisiológica de sementes, crescimento e partição de assimilados em plantas de feijão (Phaseolus vulgaris L.) tratadas com herbicidas pré-emergentes - Timm, Fabiana Carrett (2008)
The bean is a grain of great importance in the human feeding. The bean culture presents several agronomical problems, being the control of weeds of fundamental importance in the income and in the final quality of the product. This control is a lot of times made with the use of pre-emergent herbicides. Thus, the objective was to study the action of pre-emergent herbicides pendimenthalin, trifluralin e metolachlor the physiologic quality of seeds, growth and assimilates partition in bean cultivar BRS Expedito. In laboratory conditions, the physiological quality of seeds and the viability of the bean seeds cultivar BRS Expedito were reduced with the increment of the doses of all herbicides, except for the herbicide pendimenthalin that was shown less prejudicial to the viability and the vigor of bean seeds. The growth of cv. BRS Expedito bean plants in the absence of competition with weeds under greenhouse conditions suffered influence of the action of the herbicides starting from the recommended dose, emphasizing that the herbicide metolachlor prejudices the initial growth and development of the bean plants drastically. However, the used herbicides did not reduce the final accumulation of dry matter in green beans and seeds, and thus these herbicides could be recommended for the use in pre-emergence.